A correlation study of emergency department nurses' fatigue, perceived stress, social support and self-efficacy in grade III A hospitals of Xi'an. Issue 32 (7th August 2020) - Wu, Chao; Ge, Yiling; Xu, Chao; Zhang, Xinyan; Lang, Hongjuan
Abstract : Abstract: Fatigue is a universal and challenging problem in a nurse's career, particularly for those working in the emergency department. Through analyzing the current status of emergency department nurses' fatigue, the purpose of this study is to provide guidance for occupational health promotion strategies making and fatigue relief. Cross-sectional study was conducted among nurses working in emergency department in 6 grade III A hospitals in Xi'an, China. Convenience sample of 346 nurses agreed to participate in this study. Data collection was based on the questionnaires. Descriptive statistics, hypothesis tests and correlation analysis were used to describe the samples' characteristics and identify associations amongst participants' characteristics. The fatigue score of those emergency nurses from grade III A hospitals in Xian was 8.71 ± 3.01, a high fatigue level. Moreover, there were significant differences in fatigue scores of different age groups, sleep qualities, work stress levels and physical states ( P < .01). Further, the dimension of physical fatigue in various age groups, job title, marital status, sleep qualities, work stress levels and physical states was significantly different ( P < .05) and the dimension of mental fatigue with different sleep qualities, work stress levels and physical states was significantly different ( P < .01). The results of correlation analysis showed that fatigue was positively correlated with perceived stress while negatively correlated with social support and self-efficacy ( P < .01). The multiple stepwise linear regression analysis indicated that the independent variables in the fatigue regression equation were perceived stress, physical condition and work stress in turn ( P < .01), and the independent variables in the the dimensions of physical fatigue regression equation were perceived stress, physical condition, work stress and job title in turn ( P < .05); the independent variables in the the dimensions of mental fatigue regression equation were perceived stress, subjective support and physical condition in turn ( P < .05). The current status of high fatigue level of emergency nurses should be taken seriously. It is imperative to take effective measures to help emergency nurses reduce stress, improve social support, promote the self-efficacy, and thus relieve fatigue.